2021
DOI: 10.1007/s10965-021-02726-4
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional poly(vinylidene fluoride) and styrene butadiene rubber blend magneto-responsive nanocomposites based on hybrid graphene oxide and Fe3O4: synthesis, preparation and characterization

Abstract: Functional nanocomposites based on a blend of styrene butadiene rubber (SBR) and polyvinylidene di uoride (PVDF) as the matrix reinforced by a hybrid nano ller system of graphene oxide nanosheets (GOn) and ferromagnetic nanoparticles (Fe 3 O 4 ) at different weight ratios (3.75:1.25; 2.5:2.5 and 1.25:3.75) were successfully prepared and characterized to determine the effect of nano llers hybridization in improving the structural,mechanical, dielectric/electrical, magnetic and thermal properties of a polymer bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 74 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…Essabir et al [ 135 ] added graphene oxide nanosheets (GONs) and ferromagnetic nanoparticles (Fe 3 O 4 ) as hybrid fillers to hybrid nanocomposites based on SBR and polyvinylidene difluoride (PVDF). Masterbatches of PVDF/5 wt% nanoparticles (GONs and Fe 3 O 4 ) were prepared by solution mixing in dimethylformamide, followed by mechanical mixing with the matrix (PVDF/SBR blend) to obtain the final composites.…”
Section: Rubber Composites With Different Graphene Hybrid Fillersmentioning
confidence: 99%
“…Essabir et al [ 135 ] added graphene oxide nanosheets (GONs) and ferromagnetic nanoparticles (Fe 3 O 4 ) as hybrid fillers to hybrid nanocomposites based on SBR and polyvinylidene difluoride (PVDF). Masterbatches of PVDF/5 wt% nanoparticles (GONs and Fe 3 O 4 ) were prepared by solution mixing in dimethylformamide, followed by mechanical mixing with the matrix (PVDF/SBR blend) to obtain the final composites.…”
Section: Rubber Composites With Different Graphene Hybrid Fillersmentioning
confidence: 99%
“…Addition of CNTs together with poly(methyl methacrylate) can change the ability of PVDF to crystallize [40], while addition of GO and magnetic Fe3O4 [41] improves thermal stability, mechanical, electric and magnetic properties, providing promising material for magneto applications. Improving thermal conductivity is crucial for the dissipation of heat in the electronic devices [42].…”
Section: Tuning Pvdf Thermal and Electrical Propertiesmentioning
confidence: 99%
“…. Also, Essabir et al [41] concluded that GO nanosheets and Fe3O4 (added separately or as the hybrid fillers [94] to PVDF) become nucleating centers and thermal stabilizers during the β-phase formation. Similar role of nucleating centers was observed for modified using 3-aminopropyl triethoxysilane) carbon nanotubes, increasing the β-phase content by 103 % [95].…”
Section: Recent Progress In the Understating Of The α-To-β Conversionmentioning
confidence: 99%